INTANGIBLE ASSET, PROFITABILITAS, DAN SUSTAINABILITY REPORT TERHADAP NILAI PERUSAHAAN - Annisa Marwa; Deannes Isynuwardhana; Annisa Nurbaiti (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2017)
Sri-Kehati Index has been increased since 2009, though return on equity has decreased. Stock price will be affected by the ROE so that the value of the firm also decreases. In this study, the independent variables are intangible assets, profitability, and sustainability report. The dependent variable is the value of the firm. This study aims to determine the effect of intangible assets, profitability, and sustainability report on the value of the firm in a company registered in Sri-Kehati Index Indonesia Stock Exchange. The population are all companies registered in SriKehati Index in the period of 2009- 2014, while the sample is determined by purposive sampling method so as to obtain 5 companies. The analytical method used is the panel data regression analysis. The results show intangible assets, profitability, and sustainability report simultaneously significant effect on value of the firm. While partially intangible asset has significant negative effect and profitability has significant positive effect on value of the firm.